determine a operação entre polinômios : (xy-2y) - (4xy-6x)=
Soluções para a tarefa
Respondido por
0
(xy - 2y) - (4xy - 6x) =
xy - 2y - 4xy + 6x =
- 3xy + 6x - 2y
xy - 2y - 4xy + 6x =
- 3xy + 6x - 2y
Respondido por
0
Olá! :)
( xy - 2 y ) - ( 4 xy - 6 x ) = xy - 2 y - 4xy + 6 x =
- 3xy + 6 x - 2 y
Abraços e até mais! :)
( xy - 2 y ) - ( 4 xy - 6 x ) = xy - 2 y - 4xy + 6 x =
- 3xy + 6 x - 2 y
Abraços e até mais! :)
Perguntas interessantes
Português,
11 meses atrás
Português,
11 meses atrás
Matemática,
11 meses atrás
Sociologia,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás